08.31 Unravelling the role of il33/st2l axis on sustained ifn-a production in systemic lupus erythematosus. (1st March 2017) - Georgakis, Spiridon; Papadaki, Garyfallia; Gergianaki, Irene; Sidiropoulos, Prodromos; Verginis, Panagiotis; Gkirtzimanaki, Aikaterini; Bertsias, George
Abstract : Background: In Systemic Lupus Erythematosous (SLE), extracellular DNA (as in extracellular chromatin traps or immune complexes) combined with alarmins/danger- associated molecular patterns promote the production of IFNa by plasmatocytoid dendritic cells (pDCs). 123 IL-33 is a cell necrosis-derived alarmin with immunostimulatory properties which depend on the context of immune cells and inflammatory milieu. 4 We hypothesised that IL-33 might augment the interferogenic potential of extracellular DNA in SLE. Materials and methods: Human peripheral blood pDCs were isolated from SLE patients and healthy individuals and IL-33 receptor (ST2L) expression was determined by flow cytometry and RT-PCR. Oligonucleotides (CpG ODNs) were administered with/without recombinant IL-33 and IFN-a production was measured by RT-PCR and ELISA. IL-33 decoration of neutrophil extracellular traps (NETs) was examined using immunofluorescence and confocal microscopy. pDCs were stimulated with NETs-containing supernatants with/without recombinant IL-33 and IFN-a production was measured. Results: Spontaneous-released NETs from peripheral blood neutrophils of active SLE patients were decorated with IL-33 to larger extent compared to healthy-derived NETs. Circulating CD303 + /CD123 + pDCs from active SLE patients exhibited membrane expression of ST2L albeit at lower levels compared to healthy pDCs (p<0, 05). Combined CpG/IL-33 activation of pDCs promoted enhanced IFN-a mRNa and protein levels compared to CpG alone (p<0, 05). Moreover, co-administration of IL-33 and NET-containing supernatants on pDCs significantly enhanced IFN-a protein and mRNA levels (p<0, 05). Conclusions: The alarmin IL-33 produced by SLE NETing neutrophils promotes IFN-a production by pDCs therefore contributing to autoimmune inflammatory responses. Topic: Autoimmune inflammation References: Garcia-Romo, G. S., S. Caielli, B. Vega, et al . "Netting Neutrophils Are Major Inducers of Type I IFN Production in Paediatric Systemic Lupus Erythematosus." Science Translational Medicine 2011;3:73. Lande R., Gregorio J., Facchineti V., et al. ''Plasmacytoid dendritic cells sense self-DNA coupled with antimicrobial peptide.'' Nature 2007;449. Tian, Jane, Ana Maria Avalos, Su-Yau Mao, et al . "Toll-like Receptor 9–dependent Activation by DNA-containing Immune Complexes Is Mediated by HMGB1 and RAGE." Nature Immunology 2007;8.5 :487–96 Duan, Lihua, Jie Chen, Feili Gong, et al . "The Role of IL-33 in Rheumatic Diseases." Clinical and Developmental Immunology 2013:1–5.